The Echinoderm Fauna of the Azores (NE Atlantic Ocean) - Madeira, Patrícia; Kroh, Andreas; Cordeiro, Ricardo; de Frias Martins, António M.; Ávila, Sérgio P. (Zootaxa, 2019)
In more than 150 years of research in the waters surrounding the Azores, several publications on the fauna of echinoderms of the archipelago have been produced, in the form of papers, notes, reports, reviews, and monographs. This work attempts to summarize the present knowledge on this marine group in the Azorean exclusive economic zone (i.e., waters within 200 nautical miles of the archipelago’s shores). A short review of the history of the species’ taxonomy is given, with key references, geographical distribution, ecology, additional notes and, when possible, figures. We herein report 172 species of echinoderms (6 crinoids, 55 ophiuroids, 45 asteroids, 36 holothurians, and 30 echinoids) from the Azores Archipelago, most of them inhabiting deep waters (>200 m). Only 29 shallow-water species were recorded locally (≤50 m depth). In general, the echinoderm species present in the Azores are characterized by a wide geographical distribution in the Atlantic Ocean. Only nine taxa (all deep-water species, >840 m) appear to be restricted to the Azorean waters. Overall, the knowledge of the echinoderm fauna of the Azores is out-dated, with many species last collected in the archipelago over 100 years ago. A recent interest in the Azorean Mid-Atlantic waters has brought oceanographic cruises back to the archipelago, thus providing new opportunities for the renewal of 150 years of echinoderm studies in the area.